Antiemetic Use in the Emergency Department. (April 2017) - Weant, Kyle A.; Bailey, Abby M.; Baum, Regan A.; Justice, Stephanie B.; Calhoun, Chara D.
Abstract : Nausea and vomiting are 2 of the most common complaints of patients presenting to the emergency department (ED). In addition, antiemetics are the most commonly prescribed medications in the ED behind analgesics. Treating these conditions can be complex, especially as one considers that nausea and/or vomiting could be the primary presenting illness or simply a symptom of a more complex etiology. Although there is a wide variety of pharmacotherapeutic options in the armamentarium to treat these conditions, very few consensus recommendations exist to help guide the use of antiemetic agents in the ED, leading to wide variability in medication use. Contributing to these variations in practice is the extended spectrum of etiologies and potential physiological factors that contribute to the development of nausea or vomiting. A thorough understanding of the pharmacology and administration of these agents can help practitioners devise tailored antiemetic regimens based upon the underlying etiology.